Sinonasal Quality of Life Outcomes after Endoscopic Endonasal Transsphenoidal Surgery with Posterior Septum Free Mucosal Graft Reconstruction - Wu, Tara J.; Chen, Angela; Wells, Christine; Heaney, Anthony P.; Bergsneider, Marvin; Wang, Marilene B. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Quality of life (QoL) outcomes following endoscopic endonasal transphenoidal surgery (EETS) across a variety of reconstructive methods improve by 2 to 6 months. An option for sellar reconstruction, in the absence of a significant intraoperative cerebrospinal fluid (CSF) leak, is a free mucosal graft (FMG) from the posterior septum. We analyze sinonasal QoL outcomes in patients undergoing EETS with FMG reconstruction.Study Design This study was a retrospective review.Setting This study was conducted at tertiary care academic center.Participants This study group consisted of patients undergoing EETS for pituitary adenomas from 2013 to 2018.Main Outcome Measures Tumor and surgical factors were included, along with postoperative complications. Patients completed Sinonasal Outcome Test-22 (SNOT-22) questionnaires. Pre- and postoperative scores were compared among the entire cohort using linear multilevel regression. A subcohort analysis was performed among patients who completed questionnaires during the preoperative visit and two postoperative visits (within 1 month and between 2 and 3 months, respectively); pre- and postoperative total and individual domain SNOT-22 scores were compared using paired t-tests.Results A total of 243 patients underwent EETS with FMG reconstruction. Four patients (1.6%) developed a postoperative CSF leak requiring reoperation. Among the entire cohort, SNOT-22 scores increased at the first postoperative visit (p < 0.01) but returned to baseline by the second, third, and fourth postoperative visits (p = 0.27, p = 0.18, and p = 0.21). Among 48 patients who completed both preoperative and two postoperative questionnaires, scores increased within the first month (p < 0.01) but returned to baseline at 2 to 3 months (p = 0.67).Conclusion Posterior septum FMG reconstruction of sellar defects is an effective option, demonstrating early recovery of baseline sinonasal QoL by 2 to 3 months.
Keywords: endoscopic endonasal transphenoidal surgery; sellar reconstruction; free mucosal graft; quality of life; sinonasal outcome test-22; sinonasal morbidity